Isolation and Characterization of Ciprofloxacin Resistant Salmonella from the Wastes of Hospital Patients - Chowdhury, AMMA; Anwar, M Nural (Bangladesh Journal of Microbiology, 2011)
In this investigation, 12 ciprofloxacin resistant Salmonella were isolated from medical waste samples. Identified Salmonella isolates were then subjected to sensitivity analysis against five antibiotics. All the ciprofloxacin resistant Salmonella isolates were resistant to ampicillin, amoxicillin, and penicillin and were considered multidrug resistant. Growth of four ciprofloxacin resistant Salmonella from four medical samples at various concentrations (50 to 500 mg/ml) was measured. Three of four Salmonella isolates from medical samples showed growth even against 500 mg/ml of ciprofloxacin. The occurrence of these highly resistant isolates in medical samples indicated the high percentage of undigested ciprofloxacin in medical waste sample. Agarose gel electrophoresis of these 12 isolates showed no plasmid DNA band indicating that observed resistance might be chromosomal gene mediated. Key words: Hospital wastes; Salmonella; Ciprofloxacin; Multidrug resistant DOI: http://dx.doi.org/10.3329/bjm.v27i1.9160 BJM 2010; 27(1): 6-9